POTENSI PEMBERDAYAAN EKONOMI KREATIF BERBASIS POTENSI LOKAL MELALUI INOVASI OLAHAN DAUN KELOR DI DESA GONDANG - Ansori, Mufid; Apriani, Aulia; Abidin, Zaenal; Putra, Dodik; Jurnal Wicara; Ulfa, Rosiana; Satia, Merry; Yulianti, Dini; Salsabilla, Hecha; Saputro, Wira; Mauliditya, M.; Sari, Zeti (Universitas Mataram, 2025)
Gondang Village is one of the villages in Gangga District, North Lombok Regency. This village is famous for its abundant natural potential, one of which is the moringa leaf plant. Moringa leaves are one of the plants with a very high nutritional content. The use of moringa leaves as a healthy food ingredient has great potential in improving the nutritional status of the community while providing economic value through home-processed products and local potential. which aims to build the awareness and ability of the community to improve their economy through various educational and promotive activities. The expected benefits of this activity are the empowerment of the community by creating jobs for the community and gradually increasing their economy. The method used in this program is socialization and training in the manufacture and marketing and distribution of processed moringa leaves, which is carried out with the main focus on socialization of processed moringa leaves, product distribution to MSMEs and posyandu to support the health of toddlers